Evaluasi Usability Website Pelatihan Online XYZ Menggunakan Metode System Usability Scale - Rizky, Muhamad (Pusat Riset dan Inovasi Nasional, 2024)
Evaluation of the website process which aims to increase user satisfaction and can provide an evaluation of website development. The usability of this website looks at the extent of the website's usability. This research was conducted on the XYZ Online Training Website which aims to convey usefulness on the website. The method used is the system usability scale (SUS) with 10 questions to measure the usability aspects of the website. Questionnaires were used to collect data, consisting of 100 respondents consisting of Internship Participants/Alumnus and the General Audience who had visited and used the XYZ Online Training website. The results of this research found that the XYZ Online Training website had an SUS score of 46.93 which was in category f and was unacceptable. Thus, it can be said that the usability level of the XYZ Online Training website has poor usability criteria which is unreliable and unable to meet the desires and needs of its users. Then the management can improve services and improve services according to complaints experienced by users.